ANALISIS RISIKO KONTRAK TURNKEY PADA PROYEK KONSTRUKSI TRANSMISI DI INDONESIA - Sony Haryono; Betty Susanty; Mona F Toyfur (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2022)
Today, the increasing electricity demand will increase the number of electricity infrastructure developments in Indonesia. One of the electricity infrastructures is the transmission line, which transmits electricity from the power plant to the consumer. On the other hand, the limited funds owned by the owner and the various benefits that will be obtained have made a turnkey contract widely used. However, transmission line projects with a turnkey contract have just been implemented in Indonesia, so many studies have yet to be done on the risks during construction. As a result, most transmission line projects in Indonesia use traditional/non-turnkey contracts. This study aimed to identify and analyze risks that occur in transmission line projects with a turnkey contract during the construction period. This study was conducted quantitatively; risk identification was obtained from various risk variables in previous studies. The risk variables were then measured for the level of risk using a probability and impact analysis. Finally, a questionnaire was distributed to respondents who were directly involved in the construction period of the transmission line projects with a turnkey contract. The results of this study indicate the risks that occur in the transmission project with a turnkey contract. There are two risks with the highest level of risk that affect the completion time of the work, namely (i) the contractor is in financial trouble and (ii) the contractor's financial capacity is not good. It is hoped that contractors or other stakeholders can use the results of this study to mitigate before the work starts so that the project can be completed within the agreed time.